Efektivitas Biosurfaktan PKO Dalam Chemical Eor: Studi IFT, CMC, Adsorpsi, dan Toksisitas - Abdurrahman Daulay; Novia Rita; Fuja Aprida (Lembaran publikasi minyak dan gas bumi, 2025)
Palm kernel oil (PKO) is a potential raw material for biosurfactant production dua to its high content of medium-chain fatty acids, particularly lauric acid. This study aimed to synthesize methyl ester sulfonate (MES) biosurfactant from PKO and evaluate their performance in reducing interfacial tension and increasing oil recovery. Synthesis was carried out through a transesterification reaction using H2SO4 as a catalyst, followed by sulfonation. Characterization was carried out through measurement of physical properties (pH, density, viscosity), fatty acid composition (GC-MS), and FTIR analysis. Performance test included interfacial tension (IFT). Critical micelle concentration (CMC), adsorption on porous media, toxicity testing, and oil recovery test under simulated reservoir conditions (T = 50 0C, salinity 10,000 ppm). The results showed that the biosurfactant from PKO was able to reduce the IFT from 15.2 m N/m (50 ppm) to 1.2 m N/m (1000 ppm), with the CMC achieved at a concentration of 500 ppm. Biosurfactant adsorption was in the range of 28-32%, while toxicity tests showed an increase in mortality of up to 85% at 1000 ppm. Flooding tests showed an increase in oil recovery of up to 24.3% at 1000 ppm. Thus, the biosurfactant from PKO has potential as an Enhanced Oil Recovery (EOR) agent, although further studies regarding its toxicity are needed.